Voices of Midwives working in Family Physician Program Regarding Their Challenges and Blessings: A Qualitative Study - Roghieh Bayrami; Hossein Ebrahimipour; Ali Vafaee Najar (Mashhad University of Medical Sciences, 2018)
Background & aim: Midwives, as a part of the healthcare team, have a remarkable role in providing health to families and societies. Midwives have a prominent role in the family physician program (FPP); therefore, the lack of proper attention to their challenges results in a decline in their efficiency and quality of care. Therefore, this study was performed to explore the midwives' perceptions and experiences about the challenges of working in the FPP. Methods: This qualitative study was conducted on 23 midwives recruited in the healthcare centers of Mashhad, Iran, in 2015. The study population was selected using the purposive sampling technique. Data collection was performed through semi-structured in-depth interviews. The interviews were transcribed verbatim and analyzed using conventional content analysis approach. The trustworthiness of the research findings was checked by the criteria recommended by Lincoln and Guba (1985). Results: The analysis of the data led to the identification of two themes including 1) professional struggles and 2) internal reflections, each of which was further divided into several categories. Professional struggles included categories of professional autonomy, professional role ambiguity and professional commitment. Two categories of internal challenges and internal satisfaction were subsumed under the main theme of internal reflections.   Conclusion: Listening to the voices of midwives working in family physician program could provide valuable messages for policy makers to recognize the challenges of midwives in the FPP and to find the best solutions for their organizational problems and consequently enhance their efficiency in fulfillment of organizational goals.